Tensins: Bridging AMP-Activated Protein Kinase with Integrin Activation. Issue 10 (October 2017) - Georgiadou, Maria; Ivaska, Johanna
Abstract : Integrin activation is essential for cell adhesion and for connecting the extracellular matrix to the actin cytoskeleton. Thus, inappropriate integrin activation has been linked to several diseases, including cancer. Recent insights demonstrate that the main fibrillar adhesion component tensin maintains β1-integrin active in these mature adhesions. Depletion or silencing of AMP-activated protein kinase (AMPK), the energy sensor involved in maintaining the energy balance of the cell, enhances integrin activity by increasing the expression of tensin and thereby promoting cell adhesion, matrix formation, and mechanotransduction. Here, we discuss the role of tensin and AMPK in the regulation of integrin activity and integrin-dependent processes and their implication in diseases such as cancer and tissue fibrosis. Trends: The energy sensor AMPK negatively regulates gene expression of the scaffold proteins tensin 1 and tensin 3. Loss of AMPK enhances the formation of fibrillar adhesions, rich in tensin and active α5β1-integrin. Direct binding of tensins to the β1-integrin tail is required for maintaining β1-integrin activity; however, tensins support β1-integrin activity only in the presence of talin. Tensins promote cell spreading, fibronectin fibrillogenesis and traction force in the absence of AMPK. AMPK negatively regulates several proteins involved in cell adhesion and migration, either directly or indirectly.